PENGARUH STRUKTUR DEWAN KOMISARIS, KOMITE AUDIT, DAN KEPEMILIKAN ASING TERHADAP TAX AVOIDANCE - Marsya Wardani Herlanda, (2021)
This study aims to analyze the effect of the structure of the board of commissioners, audit committee, and foreign owners on tax avoidance. Measurement of Tax Avoidance in this study is Abnormal Book Tax Different (ABTD). Samples were taken from manufacturing companies listed on the Indonesia Stock Exchange for the period 2017-2019 with a purposive sampling method so as to obtain 24 samples of companies. The data analysis technique used Multiple Linear Regression Analysis. The results showed: (1) female board of commissioners had no effect on tax avoidance, (2) audit committee had no effect on tax avoidance, (3) foreign ownership had a negative effect on tax avoidance. This finding shows that the presence of foreign ownership in the subsample companies can reduce tax avoidance.